2013
DOI: 10.1002/j.2168-0159.2013.tb06128.x
|View full text |Cite
|
Sign up to set email alerts
|

4.3: Invited Paper: High Mobility Oxide TFT for Large Area High Resolution AMOLED

Abstract: The adoption of bi‐layered etch stop layer (BiESL) for oxide thin film transistor with high carrier mobility was proposed for the application to the large area high resolution AMOLED. A novel bi‐layered etch stop structure composed of Al2O3/SiO2, in which thin and dense Al2O3 film prepared by atomic layer deposition was deposited on the PECVD SiO2 layer. High mobility of In‐Ga‐Zn‐O TFT with the proposed BiESL showed no significant change in turn‐on voltage, even without passivation film. The field‐effect satur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In oxide TFTs, active layers with a higher carrier concentration are preferred because the mobility is proportional to the carrier concentration [1], but V th control difficulty simultaneously occurs [2]. The oxygen vacancy and hydrogen in oxide semiconductors are mainly regarded as sources of charge carrier.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In oxide TFTs, active layers with a higher carrier concentration are preferred because the mobility is proportional to the carrier concentration [1], but V th control difficulty simultaneously occurs [2]. The oxygen vacancy and hydrogen in oxide semiconductors are mainly regarded as sources of charge carrier.…”
Section: Introductionmentioning
confidence: 99%
“…The source of hydrogen in the active layer can be any of the following: (1) ambient atmosphere; (2) incorporation during the deposition of an active layer, such as the gate insulator or passivation layer; and (3) diffusion from the adjacent layers with an active layer during post-annealing. The first can be negligible when a passivation layer is adopted, but the other sources occur very often during the fabrication of oxide TFTs.…”
Section: Introductionmentioning
confidence: 99%
“…However, the maximum value of carrier mobility was obtained to be no more than 15 cm 2 /V s, which was regarded as too a low value to meet severe mobility specifications for highly functional applications such as super Hi-vision 25 and glass-free 3D TV. 26 In these next-generation FPD applications, the carrier mobility should be improved to be higher than 25 cm 2 /V s for securing sufficient current drivability. 27,28 Thus, it is an urgent issue to enhance the carrier mobility of the TFTs exploiting the ALD-IGZO channel layers, and two technical approaches can be implemented.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the target application, for example, OLED displays, high barrier performance may be required during the TFT backplane fabrication process. Some researchers have reported that AlO layers formed by atomic layer deposition (ALD) offer excellent barrier performances . However, the ALD method provides limited productivity and limited substrate size scalability because of difficulty in performing deposition over large substrate areas within a suitably productive deposition time.…”
Section: Introductionmentioning
confidence: 99%